Implementing REDD+ (Reducing Emissions from Deforestation and Degradation): evidence on governance, evaluation and impacts from the REDD-ALERT project - Matthews RB; Noordwijk, Meine van; Lambin, E.F.; Meyfroidt, Patrick; Gupta J; Verchot, Louis V.; Hergoualc'h, Kristell; Veldkamp, E. (Springer, 2014)
The REDD-ALERT (Reducing Emissions from Deforestation and Degradation from Alternative Land Uses in the Rainforests of the Tropics) project started in 2009 and finished in 2012, and had the aim of evaluating mechanisms that translate international-level agreements into instruments that would help change the behaviour of land users while minimising adverse repercussions on their livelihoods. Findings showed that some developing tropical countries have recently been through a forest transition, thus shifting from declining to expanding forests at a national scale. However, in most of these (e.g. Vietnam), a significant part of the recent increase in national forest cover is associated with an increase in importation of food and timber products from abroad, representing leakage of carbon stocks across international borders. Avoiding deforestation and restoring forests will require a mixture of regulatory approaches, emerging market-based instruments, suasive options, and hybrid management measures. Policy analysis and modelling work showed the high degree of complexity at local levels and highlighted the need to take this heterogeneity into account—it is unlikely that there will be a one size fits all approach to make Reducing Emissions from Deforestation and Degradation (REDD+) work. Significant progress was made in the quantification of carbon and greenhouse gas (GHG) fluxes following land-use change in the tropics, contributing to narrower confidence intervals on peat-based emissions and their reporting standards. There are indications that there is only a short and relatively small window of opportunity of making REDD+ work—these included the fact that forest-related emissions as a fraction of total global GHG emissions have been decreasing over time due to the increase in fossil fuel emissions, and that the cost efficiency of REDD+ may be much less than originally thought due to the need to factor in safeguard costs, transaction costs and monitoring costs. Nevertheless, REDD+ has raised global awareness of the world’s forests and the factors affecting them, and future developments should contribute to the emergence of new landscape-based approaches to protecting a wider range of ecosystem services.